Remanescentes das comunidades de quilombos, da resignificação ao imperativo legal - Carlos Eduardo Marques (2008)
The thesis is divided into two parts and five chapters. The first part seeks to assess what has historically been defined as quilombo as well as demonstrate the need to overcome this vision passadista and frigorificada of term. It also seeks to understand how the historical process, academic and activist allowed to re-meaning of that term. It demonstrates that for the conformation of the new term, it was necessary to merge the four speeches. Speeches, which are together with their respective actors, in a context of struggle that considers itself as affirmative struggles in the field are theoretical or in the political arena. Finally it is shown that such fields form a single reality, their separation is a methodology for better understanding. In the second part of the dissertation seeks to examine the legal and conceptual issues regarding the word quilombo. For both, to elect two topics that are considered essential to the understanding of this issue: a number of legal aspects, and the concept of the idea of territory as a locus ethnic. Through textual analysis, legislation and literature about the concept of territory, seeks to demonstrate that: 1 - the preponderance of the classification should focus on the very subject, seen from its reality, its organization and its conflicts , 2 - the centrality of ethnography, understood as a construct, on which it is possible to the theoretical work of re-meaning the idea of remaining in and quilombos, 3 - the importance of the domain ofconcepts - be they developed from the vision ethnographic, whetherdeveloped from a political militancy - for drawing up the new joint legal and conceptual to the category of Remanescentes Quilombos.